Performance of AIS, Organizational Performance, User Motivation on Reporting Accountability at the Department of Trade, Cooperatives, and SMEs of Klaten Regency - Putra Zai, Simon Nisja; Jumarni, Jumarni (PT. Anagata Sembagi Education, 2024)
This study aims to examine the effect of the use of Accounting Information Systems (AIS), organisational performance, and user motivation on performance accountability at the Klaten Regency Cooperative and SME Office. The research sample consisted of 58 respondents involved in this study. Data were collected through questionnaires distributed to AIS users in the agency and have passed classical assumption testing. The results showed that the use of AIS has a positive effect on performance accountability, indicating that effective information systems can improve accountability in the department. However, organisational performance does not have a significant effect on accountability at the Klaten Regency Industry, Cooperatives and SMEs Office. In contrast, user motivation was shown to have a significant positive influence on accountability. These findings indicate the importance of user motivation in improving performance accountability, whereas organisational performance does not directly affect accountability in this context. Future research is recommended to consider organisational culture factors and explore how to increase commitment to system use. In addition, researchers are encouraged to use more comprehensive elements and broader testing methods for more in-depth results.